2019
DOI: 10.1021/acsomega.9b00127
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Tandem Drug/Mesoporous Silicon Microcarrier Structures for Anti-Inflammatory Therapy

Abstract: The properties of nanostructured plant-derived porous silicon (pSi) microparticles as potential candidates to increase the bioavailability of plant extracts possessing anti-inflammatory activity are described in this work. pSi drug carriers were fabricated using an eco-friendly route from the silicon accumulator plant bamboo (tabasheer) powder by magnesiothermic reduction of plant-derived silica and loaded with ethanolic extracts of Equisetum arvense , another silicon accumulator plant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These choices include tabasheer (a silica-rich extract present in bamboo), rice husk, and horsetail (Equestium). Our groups’ collaboration [ 45 , 46 , 47 , 48 ] have demonstrated that pSi derived from magnesiothermic reduction of these plant sources can produce nanostructures for drug delivery. Other research groups [ 49 , 50 , 51 , 52 , 53 , 54 ] have focused on anode material for lithium batteries.…”
Section: Porous-silicon Synthesis—the Need For Sustainable Approacmentioning
confidence: 99%
“…These choices include tabasheer (a silica-rich extract present in bamboo), rice husk, and horsetail (Equestium). Our groups’ collaboration [ 45 , 46 , 47 , 48 ] have demonstrated that pSi derived from magnesiothermic reduction of these plant sources can produce nanostructures for drug delivery. Other research groups [ 49 , 50 , 51 , 52 , 53 , 54 ] have focused on anode material for lithium batteries.…”
Section: Porous-silicon Synthesis—the Need For Sustainable Approacmentioning
confidence: 99%
“…The XRPD offers a complementary way of assessing the crystallinity of confined compounds [19,25,28,29,[31][32][33]. Like DSC, XRPD can be used to determine if the confined drug is in its crystalline or amorphous state.…”
Section: Crystallisation Characterisation Techniquesmentioning
confidence: 99%